2023
DOI: 10.1021/acs.analchem.3c00687
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Aluminum–Metal Organic Framework/HEPES Electrochemiluminescence System for Ultrasensitive Detection of HBV DNA

Abstract: In this work, a novel aluminum metal–organic framework (Al-MOF)/N-2-hydroxyethylpiperazine-N′-ethane-sulfonic acid (HEPES) system with an excellent electrochemiluminescence (ECL) property was developed. First, Al-MOF was successfully synthesized through a one-pot solvothermal method by using 9,10-di(p-carboxyphenyl)anthracene (DPA) as the organic luminescence ligand and Al3+ as the metal node. Compared with DPA, Al-MOF showed high ECL intensity and excellent stability without an additional coreactant in the HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…First, Zr-DPA and Zr-DPA@TCPP exhibited similar ECL properties, which had anodic ECL signals and almost no cathodic ECL emission in HEPES (curve a , b ). In our previous work, it was demonstrated that HEPES, as the more environmentally friendly and less toxic anode coreactant than conventional tripropylamine (TPrA), can interact with the DPA-based MOF to generate ECL . Here, similarly, the anodic ECL of Zr-DPA@TCPP was attributed to the interaction between HEPES and the Zr-DPA structure.…”
Section: Resultsmentioning
confidence: 99%
“…First, Zr-DPA and Zr-DPA@TCPP exhibited similar ECL properties, which had anodic ECL signals and almost no cathodic ECL emission in HEPES (curve a , b ). In our previous work, it was demonstrated that HEPES, as the more environmentally friendly and less toxic anode coreactant than conventional tripropylamine (TPrA), can interact with the DPA-based MOF to generate ECL . Here, similarly, the anodic ECL of Zr-DPA@TCPP was attributed to the interaction between HEPES and the Zr-DPA structure.…”
Section: Resultsmentioning
confidence: 99%
“…As ECL does not require a light source, it simplifies the detection apparatus, and, most importantly, invalidates background signals from scattered light and luminescent impurities, thus providing improved sensitivity. However, some specific ECL configu-rations employing semiconductors and named photo-induced ECL require an excitation light to photo-generate holes and electrons that trigger the emission of ECL [48][49][50]. These properties have resulted in ECL becoming a significant detection method in analytical chemistry and microscopy [23,30,[51][52][53][54][55][56][57][58][59][60].…”
Section: Ecl Sensorsmentioning
confidence: 99%
“…The high sensitivity of ECL sensors based on MOF luminophores allows the efficient detection of water pollutants, which are typically present in low amounts in water bodies. This set off the recent development of novel MOF materials for ECL and new applications, especially sensing and imaging [35,39,[44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond this accomplishment, analysts ventured out to challenge the typical binary settings (e.g., Ru(bPy) 3 2+ +TPrA) for a much biosafer and simplistic scheme as “coreactant-free” (Table S2). Although being essentially nominal, this novel characteristic indeed contributed to a generalized pool of “procoreactants”, which so far involved coreactable electrolytes (HEPES (piperazine)), precursory passivators (relay radical regeneration during the surface-state ECL of Au clusters), and so on. , Jointly, such uses of multitasking sensitizers illuminated a holistic methodology toward compact yet low-loss ECL imager setups, which shall surely be flexible and applicable to more mainstream scenarios that contemporarily predominated by epifluorescence and CL …”
Section: Introductionmentioning
confidence: 99%